The central bank strikes back! Credibility of monetary policy under fiscal influence - Antoine Camous; Dmitry Matveev (Bank of Canada, 2022)
How should independent central banks react if pressured by fiscal policymakers? We study an environment with strategic monetary-fiscal interactions where the central bank has a limited degree of commitment to follow policies over time and the fiscal authority has none. We contrast the implications of two monetary frameworks: one where the central bank follows a standard rule aiming exclusively at price stability against the other, where monetary policy additionally leans against fiscal influence. The latter rule improves economic outcomes by providing appropriate incentives to the fiscal authority. More importantly, the additional fiscal conditionality can enhance the credibility of the central bank to achieve price stability. We emphasize how the level and structure of government debt emerge as key factors affecting the credibility of monetary policy with fiscal conditionality.
Keywords: E02; E52; E58; E61; E62; 330; Monetary policy; Fiscal policy; Credibility